SISTEM MONITORING VOLUME DAN BERAT SAMPAH PADA ALAT PEMILAH SAMPAH ORGANIK DAN ANORGANIK BERBASIS INTERNET OF THINGS MENGGUNAKAN APLIKASI BLYNK - Salamah, Annisa; Kusumanto, RD; Evelina (JURNAL TELISKA, 2023)
Currently the accumulation of waste due to bad management will certainly polute the environtment, especially in residential areas. For this reason, a system is needed that can help manage thus waste so that is runs well. This study aims to design and bulid a system that will help to monitoring the weight and volume of waste based on the Internet of Things (IoT) to make it easier for waste workers to know when the waste is full and must be disposed of immediately to a landfill. This monitoring system is uses a load cell weight sensor and ultrasonic sensor JSN-SR04T which is instaleed on the organic and inorganic waste box that integrated with the internet via the NodemCU ESP8266 and controlled by the Arduini Uni microcontroller. This system can measure the weight and volume of waste in real time and send notifications when the waste box is full from a test disatance of 1 km.